Increasing cord atrophy in early relapsing-remitting multiple sclerosis: a 3 year study. Issue 1 (16th December 2005) - Rashid, W; Davies, G R; Chard, D T; Griffin, C M; Altmann, D R; Gordon, R; Thompson, A J; Miller, D H
Abstract : Objectives: Previous studies have shown that upper cervical cord atrophy (UCCA) occurs in multiple sclerosis (MS), particularly in those disabled and with primary or secondary progressive disease. It is less clear how early it can be detected in relapsing-remitting (RR) MS, and whether early cord atrophy relates to the concurrent or future clinical course. Methods: Twenty seven RR MS patients (median disease duration 1.7 years, in all cases <3 years from onset) were recruited along with 20 controls. They were followed for up to 3 years with a yearly assessment of UCCA and clinical function measured by the Expanded Disability Status Scale (EDSS) and MS Functional Composite Score (MSFC). Clinical and MRI correlations were investigated. Statistical models adjusted for covariates including total intracranial volume. Results: Longitudinal analysis showed a significant decrease in UCCA in patients both within the patient cohort (p<0.001) and in comparison with controls (p = 0.001). There was a significant increase in EDSS (p = 0.008) but no significant change in MSFC. The rate of UCCA loss did not correlate with clinical change or with change in brain volume. Conclusions: In summary, serial UCCA measurement detects the development of spinal cord atrophy in clinically early RR MS.